КОЛЛЕКТИВЛАШТИРИШ ГИРДОБИ ВА УНГА ҚАРШИ ДЕҲҚОНЛАР ҚИСМАТИ - Якубов, Ў.Ш.; Утепова, Г.Б. (SCIENCE and SOCIETY, 2024)
This article tells about the sad fate of the Uzbek people as a result of popular protest and Bolshevik violence against them, which arose during the process of collectivization and collective farming.
Keywords: collectivization; collective farms; kulaks; political repressions; “state of emergency”; violence; repressions